Persistence in the price-to-dividend ratio and its macroeconomic fundamentals - Malte Rengel; Helmut Herwartz; Fang Xu (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Persistent variations in the log price-to-dividend ratio (PtDR) have triggered a lively discussion in the literature. This paper proposes a present value model incorporating this persistence through a time-varying steady state of the PtDR. Log-likelihood statistics confirm that the time-varying state model outperforms its counterpart with a constant steady state. It is shown that the steady state of the PtDR is jointly influenced by consumption risk, risking sharing, and the demographic structure. Among those consumption risk is the dominating factor in shaping the variations in the steady state of the PtDR throughout the entire last century.
Keywords: E44; G01; G12; 330